Control of the amplification convertase of complement by the plasma protein beta1H. - Weiler, J M (1976)
An inhibitory activity for an erythrocyte in termediate bearing the properdin (P)-stabilized amplification C3 convertase, PC3bBb, was recognized in whole normal human serum and separated from C3b inactivator by its distinct physicochemical and functional characteristics. The inhibitory activity was found to reside in a protein that was purified to homogeneity and elicited a monospecific antibody in a rabbit. This protein was identified as beta1H and found to have a serum concentration of 516 +/- 89 mug/ml (mean +/- 1 SD). beta1H produced a dose related, first-order loss of convertase function and release of 125I-Bb from the P-stabilized intermediate, indicating a mechanism of action by decay-dissociation of Bb from the complex, PC3bBb. beta1H exhibited only a limited capacity to accelerate decay of C3bBb sites stabilized with C3 nephritic factor or to release 125I-Bb from such sites. Amplification of C3 cleavage by C3bBb may well determine whether initial complement activation by the classical or alternative activating sequence is beneficial or detrimental to the host. Regulation of this amplifying function is now recognized to occur at at least three steps: intrinsic decay which reflects the inherent lability of the C3bBb convertase; extrinsic decay-dissociation of Bb which is mediated by the effect of beta1H; and inactivation of exposed C3b by C3b inactivator. The stabilization of C3bBb by activated properdin minimizes intrinsic decay and protects C3b in the bimolecular complex from C3b inactivator. beta1H restores control of the system by decay-dissociation of the bimolecular complex, therby exposing C3b to C3b inactivator whose irreversible action prevents regeneration of the convertase at that site.